Applications and interviews: A structural analysis of two-sided simultaneous search - Ronald P. Wolthoff (Institute for the Study of Labor (IZA), 2010)
A large part of the literature on frictional matching in the labor market assumes bilateral meetings between workers and firms. This ignores the frictions that arise when workers and firms meet in a multilateral way and cannot coordinate their application and hiring decisions. I analyze the magnitude of these frictions. For this purpose, I present an equilibrium search model of the labor market with an endogenous number of contacts between workers and firms. Workers contact firms by applying to vacancies, whereas firms contact applicants by interviewing them. Sending more applications and interviewing more applicants are both costly activities but increase the probability to match. In equilibrium, contract dispersion arises endogenously and workers spread their applications over the different types of contracts. Estimation of the model on the Employment Opportunities Pilot Projects data set provides values for the fundamental parameters of the model, including the cost of an application, the cost of an interview, and the value of non-market time. These estimates are used to determine the loss in social surplus compared to a Walrasian world. Frictions on the worker and the firm side each cause approximately half of the 4.7% loss. There is a potential role for activating labor market policies, because I show that for the estimated parameter values welfare is improved if unemployed workers increase their search intensity.
Keywords: J64; J31; E24; D83; 330; labor; search; recruitment; frictions; efficiency